Simultaneous Determination of γ-Oryzanol in Agriproducts by Solid-Phase Extraction Coupled with UHPLC–MS/MS - Lv, Lei; Zhang, Liangxiao; Gao, Mengxiang; Ma, Fei (Agriculture (Basel), 2023)
In this work, a simple, rapid and cost-effective method for the simultaneous quantification of two major γ-oryzanol components in agriproducts was established by silica solid-phase extraction (SPE) coupled with UHPLC–MS/MS. Silica SPE sorbents consist of unbonded silica gel with high polarity and can retain most of the analytes with acidic properties. Silica sorbents are cost-effective materials and that can be prepared simply without a large volume of toxic chlorinated solvent. Silica SPE sorbents were utilized to extract and purify cycloartenyl ferulate (CF) and 24-methylene cycloartanyl ferulate (24-CF) in cereal products. Various parameters affecting the isolation recoveries were studied. By coupling with ultra-high-performance liquid chromatography–mass spectrometry (UHPLC–MS/MS), a novel method for the quantification of CF and 24-CF in agriproducts was developed and validated. The procedure used silica sorbent to purify the analytes in 30 min without complicated steps, which improved the simplicity and efficiency. The limits of quantification and the limits of detection of CF and 24-CF were 0.3 and 1.0 μg kg−1, respectively. Extraction recoveries ranged from 86.93% to 108.75% with inter-day and intra-day precisions less than 10.84%. The results of 50 agriproducts indicated that the rice bran had the highest averaged amount of 34.3 × 103 μg kg−1 for CF and 42.6 × 103 μg kg−1 for 24-CF, making it a perfect source of human nutritional supplement substances from agriproducts.